Proposal for a higher education admission management system with the use of open source technologies - Alturas, B.; Marimbique, J. (IADIS International Journal on Internet/WWW, 2020)
Higher education institutions are characterized by the growth of the student population, the need to align their programs with market demand, and the adoption of new management and service delivery techniques, making it essential to use information technologies. This research project aims to design an information system prototype for a higher education admission management information system and propose open source software engineering tools that can assist its development. This paper presents the main concepts related to information systems, higher education and open source software. The prototype was designed following the object-oriented software development methodology and the software engineering tools were based on the comparison of two tools to three information system software elements namely forms, reports and web portal.